Teachers’ Educational Interventions in Addressing Bullying Behavior Among Students in Public Elementary Schools in Pulubala Subdistrict, Gorontalo Regency - Bouti, Riyon; Wantu, Sastro M; Mahmud, Ramli (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to analyze classroom teachers’ interventions in preventing and addressing bullying behavior among elementary school students, as well as to identify factors influencing the effectiveness of these interventions in creating a safe and inclusive learning environment. Methodology: A qualitative approach using a case study design, purposive sampling technique, and data sources: school principals, fifth-grade teachers, and students at SDN in Pulubala District. Data collection was conducted through semi-structured interviews, observations, and document analysis. Data analysis utilized the Miles and Huberman interactive model (data reduction, data presentation, and drawing conclusions), as well as triangulation of sources, techniques, and time. Main Findings: Teacher interventions were implemented through three primary forms: as an advisor, role model, and integrated facilitator. The effectiveness of interventions was determined by factors including the emotional bond between teachers and students, interpersonal communication skills, the integrity and consistency of teachers’ behavior, as well as school environment support and parental involvement. Verbal bullying was the most dominant form, while collaborative approaches and inclusive learning proved effective in reducing bullying behavior Novelty/Originality of this study: This study offers an integrative teacher intervention model based on local empirical data by combining the roles of advisor, role model, and facilitator. This study reinforces a contextual approach in bridging the gap between normative character education and actual bullying prevention practices in elementary schools